(untitled) (Jahangirnagar University Journal of Biological Sciences, 2016)
Respiratory Tract Infections (RTIs) are major causes of illness, doctor visit and high rates of antibiotic prescriptions in Bangladesh. Over the past decades, emergence of antibiotic resistance has been recognized as an important public health problem across the globe. The current study was aimed to assess the physicians prescribing pattern of antibiotics in treating RTIs, their usages by patients and physicians opinion regarding the causes of antimicrobial resistance. This cross sectional survey was conducted by a self-designed standard questionnaire and data were collected manually over a two-month period from November 15, 2013 to January 18, 2014 in four cities of Bangladesh: Dhaka, Chittagong, Rajshahi and Khulna. According to physicians opinion, the most frequently prescribed antibiotic for RTIs was levofloxacin (33.44%) followed by azithromycin (24.12%), cefixime (18.33%) and ceftriaxone (17.84%), respectively. Erythromycin was found to be the most resistant antibiotic (32.13%). Two or more antibiotics were prescribed in 43.94% of prescriptions. A total of 65.15% prescriptions had complete direction for antibiotics use and 46.97% patients completed full course of antibiotics. Although 86.36% prescriptions had no clinical test for using antibiotics, the percentages of patients disease recovery were 84.85% and noncompliance was 15.15%. Most of the physicians believed that self-medication of antibiotics results in the spread of bacterial resistance to antibiotics in RTIs. The present findings are important for public awareness and education in antibiotic use. These findings also have significance to the regulations of prescribing antibiotics in RTIs in Bangladesh. Jahangirnagar University J. Biol. Sci. 4(2): 9-17, 2015 (December)